Disrupting Higher Education: Assessing the Impact of COVID-19 on Higher Education Institutions in Indonesia and the United States - Tristan Prodjomaroeto; Ali Muhyidin (JPP (Jurnal Pendidikan dan Pembelajaran), 2020)
This paper examines the impact of COVID-19 on higher education institutions in Indonesia and the United States using qualitative document analysis dedicated to higher education institutions. The findings suggest that the perplexing problems found in higher education institutions have downcutting the ability to achieve equal distribution of quality education, and the crisis caused by COVID-19 has made higher education less accessible specifically towards under-privileged students. Hence, the utilization of EdTech is pivotal in creating equal access and distribution in higher education. It is expected that the prevalent use of such technology is expected to stick in the long run.